Prospect Theory and the Disposition Effect - Kaustia, Markku (Journal of Financial and Quantitative Analysis, 2010)
Abstract This paper shows that prospect theory is unlikely to explain the disposition effect. Prospect theory predicts that the propensity to sell a stock declines as its price moves away from the purchase price in either direction. Trading data, on the other hand, show that the propensity to sell jumps at zero return, but it is approximately constant over a wide range of losses and increasing or constant over a wide range of gains. Further, the pattern of realized returns does not seem to stem from optimal after-tax portfolio rebalancing, a belief in mean-reverting returns, or investors acting on target prices.